Hydrogeochemical evolution in the different shallow aquifers of central gangetic plain and kosi alluvial fan and their implications for the distribution of groundwater arsenic - Mukherjee, Abhijit (2015)
For a long time it was understood that the extent of the arsenic (As) enriched groundwater is confined within the lower Ganges plain and delta in eastern India. However, during the last few years, reports of elevated As in groundwater of different parts of the middle portions of the Gangetic plain, upstream from West Bengal, in U.P. (Ramanathan et al. Geol Soc Am Program Abstr 38(7):241, 2006) and Bihar, got published. Subsequently, As contamination was detected in foothills of Himalayas in Nepal (Shrestha et al. J Environ Sci Health Part A 38(1):185-200, 2003), which is a sediment provenance for many of the tributaries of the Ganges, and also in the Indus alluvial plains in Punjab and Sindh provinces of Pakistan (Nickson et al. Appl Geochem 20(1):55-68, 2005). In spite of some surveys on As distribution, there is a lack of hydrogeochemical knowledge about the distribution, extent, severity, source and cause of the contamination in these areas. However, initial estimates show that the poisoning might be widespread and several million people may be at risk.